Application of process mining on the example of an authorized passenger car service station in Poland - Agnieszka Bitkowska; Piotr Sliż; Candace Tenbrink; Aleksandra Piasecka (Foundations of Management, 2020)
Developing new technologies pose challenges for modern organizations, including service organizations. The main goal of the article was to present the results of exploration of the passenger car repair process using the Celonis Snap program in the example of an authorized service station. Realization of the main goal was assigned to a partial goal, which was to approximate and present the existing state of knowledge regarding process mining. The following research methods were used in the research procedure: systematic review of the literature on the subject and participant observation. Process mining was performed using the Celonis Snap program. The first section of the article, which is of epistemological character, presents the assumptions of process mining. The next one characterizes the empirical structure of the organization under study and the data generated in it. In the following sections, the course of the exploration process of the repair process, results and directions of further research are presented.
Keywords: L620; L250; L840; 650; business process; process maturity; process mining; process discovery; after-sales; automotive